The pre-investigation stage of the ICC : criteria for situation selection - Stegmiller, Ignaz (Beiträge zum internationalen und europäischen Strafrecht, 2011)
Hauptbeschreibung With the first part of this study Ignaz Stegmiller provides an introduction to the problem of pre-investigations, the second part gives an overview of the OTP's structure. Part III addresses how the selection process is performed. In this part, the complexity of pre-investigations is revealed. The three trigger mechanisms - State referrals, SC referrals, and the proprio motu mechanism - are illustrated, Self-referrals are critically analyzed and the author argues that the Prosecutor should use his proprio motu power more frequently. Perceptions of OTP's la.